Targeting protein tyrosine phosphatase SHP2 for therapeutic intervention. (August 2014) - Butterworth, Sam; Overduin, Michael; Barr, Alastair J
Protein tyrosine phosphatases have been the focus of considerable research efforts aimed at developing novel therapeutics; however, these targets are often characterized as being 'undruggable' due to the challenge of achieving selectivity, potency and cell permeability. More recently, there has been renewed interest in developing inhibitors of the tyrosine phosphatase SHP2 ( PTPN11 ) in the light of its broad role in cancer, specifically juvenile myelomonocytic leukemia, and recent studies that implicate SHP2 as a key factor in breast cancer progression. Recent significant advances in the field of SHP2 inhibitor development raise the question: are we on the verge of a new era of protein tyrosine phosphatase-directed therapeutics? This article critically appraises recent developments, assesses ongoing challenges and presents a perspective on possible future directions.